The first two months epidimiological study of COVID-19, related public health preparedness, and response to the ongoing epidemic in Pakistan. (September 2020) - Kakakhel, M.A.; Wu, F.; Khan, T.A.; Feng, H.; Hassan, Z.; Anwar, Z.; Faisal, S.; Ali, I.; Wang, W.
Abstract: As an underdeveloped country, the coronavirus disease 2019 (COVID-19) epidemic has posed a major risk to the health and economy of Pakistan. The SIR (susceptible–infected–recovered) model of epidemiologic analysis predicts that there should have been more cases since late March 2020 in Pakistan. We therefore sought to investigate COVID-19's prevalence and epidemiologic trends in Pakistan. Research for COVID-19 is still in its early stages, so data were collected from official websites and research journals, then analyzed for the disease's prevalence, epidemiology, mortality and recoveries. The results indicated that a rapid increase had indeed occurred in the number of COVID-19 infections in Pakistan, with the first case reported on 25 February, 2020. From 25 February 25 to April, 2020, COVID-19 infected 11, 155 people in Pakistan, with 237 deaths (2.12%) and 2527 recoveries (19.96%). We found a statistically significant positive correlation between the prevalence of COVID-19 and the mortality ratio ( r  = 0.983, r 2  = 0.966; p ≤ 0.05). We concluded that proper management must be undertaken to improve the quarantine system, and the World Health Organization guidelines must be closely followed to cope with COVID-19. There is no vaccine for COVID-19, so antiviral drugs (interferon alfa, ribavirin) may be useful to prevent COVID-19; however, severe control measures implemented in China have significantly mitigated the spread of COVID-19. Suspected and confirmed cases must be treated in separate rooms. Staying home and social distancing are the safe way to proceed. Highlights: A novel coronavirus emerged in December 2019. Yet there is limited knowledge and information regarding COVID-19 transmission. Bat and Snake may be possible carrier of COVID-19. Flu, sore throat, fever and fatigue are the initial signs and symptoms.